Spatial Pattern of Underground Space Development in Major Cities in China: Evaluation and Analysis. (24th December 2021) - Hong, Xiaochun; Ji, Xiang
Abstract : Underground space development has gradually become an organic part of China's urban development and construction. Comprehensively developing underground space scientifically and rationally to give full play to its comprehensive benefits is the main problem faced by China's underground space development at this stage. This research starts with the measurement of the level of urban underground space (UUS) development. This paper constructs a UUS development level measurement indicator system, which is composed of Construction of UUS (D1), urban economic development indicators (D2), and urban population development indicators (D3), which has 12 secondary indicators, and then we use entropy-TOPSIS method to quantitatively evaluate the development level of underground public space in 39 prefecture-level cities and above in my country and analyze its spatial differentiation. The results show that the urban agglomeration has the characteristics of "high-high" cluster distribution with the development level of underground space. However, the overall level of underground space development in China's major cities is not high and there are apparent differences in the level of UUS development. In terms of spatial distribution, the sustainable development level of cities in the eastern coastal regions of China is relatively high, with towns in the central and northeastern areas ranking second and western towns and northeastern cities ranking the lowest. At the same time, we found that there is a mismatch between the underground space development index and the economic population development index in the evaluation index. Finally, some suggestions are put forward to realize the balanced development of UUS development in our country.